Analysis of indication of caesarean sections according to Robson’s ten group classification system at a tertiary care teaching hospital in South Rajasthan - Saharan, Saroj; Rastogi, Radha; Chyaunal, Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was categorization and evaluation of the caesarean section rate at our institute as per Robson’s formula. Methods: This retrospective study was conducted at department of obstetrics and gynecology, RNT Medical college, Udaipur, a tertiary care teaching hospital in South Rajasthan. The data was collected retrospectively from December 2020 to February 2020 over a period of 2 months and percentage were calculated in various groups as per Robson’s ten group classification system. Results: Among a total of 1195 women delivered during study period, 420 (35.14%) delivered by CS. Women with previous CS (group 5) contributed maximum (35.95%) to the total number of CS followed by group 2 (27.14%). Conclusions: Standardization of indication of caesarean deliveries, regular audits and definite protocol in hospitals will aid in curbing the rate of caesarean deliveries in hospitals.